Choosing the right treatment for patients with psoriatic arthritis. (October 2020) - Noviani, Maria; Feletar, Marie; Nash, Peter; Leung, Ying Ying
Psoriatic arthritis (PsA) is a chronic inflammatory condition with articular and extra-articular manifestations: peripheral arthritis, axial disease, enthesitis, dactylitis, psoriasis, inflammatory bowel disease and uveitis. Anti-tumour necrosis factors (anti-TNFs) have demonstrated clinical efficacies exceeding those of conventional disease-modifying antirheumatic drugs (DMARDs). New understanding in pathogenic pathways have led to novel therapeutic targets. The current treatment paradigms emphasize early diagnosis and treatment, and treating towards remission and low disease activity status, particularly in long-standing disease. This review addresses the evidence of current treatment options for each of the domains of PsA. We present a simple guide that weighs on clinical efficacies for each PsA domain to aid clinicians in choosing the most appropriate treatment for patients. We highlight the unmet need for biomarkers of treatment response, and future perspectives with precision medicine in PsA.